Розробка компонентів системи автоматизації процесів управління зоопарком на платформі Appian - Галюк, Д. Ю. (ХНУРЕ, 2024)
This project is dedicated to the creation of zoo management process automation system components using the Appian platform. System provides an authenticated user a possibility to manage zoo processes, create work tasks for different types of workers and look through performance reports of the zoo. An Appian BPM (business process management) low-code platform was used for creation of a system. Each type of user has its own interfaces. This makes the application suitable for every worker who has its own tasks.
Keywords: автоматизація процесів; управління зоопарком; платформа Appian; система автоматизації